Concentration of Phenolic Compounds and Phenolic Acids of Various Spelt Cultivars in Response to Growing Years - Magdaléna Lacko-Bartošová; Amandeep Kaur; Lucia Lacko-Bartošová; Ľubomír Kobida; Matej Hudec; Jan Moudrý (Agriculture, 2023)
The aims of this study were to evaluate and compare the radical scavenging activities (DPPH), phenolic concentrations and concentrations of selected phenolic acids (PAs) of spelt cultivars and breeding lines with common wheat in a three-year controlled field experiment under conditions of organic farming. No significant variations were observed in the total and free DPPH of Altgold, Ebners Rotkorn, Ostro and PN-1-36 with common wheat. The total DPPH ranged from 52.13% to the lowest value of 44.01% in Franckenkorn. Total, free and bound phenolic concentrations were the highest for common wheat (1902.55 µg FAE g−1 DM of total), while all spelt cultivars achieved significantly lower values (from 1434.94 µg FAE g−1 DM in Franckenkorn to 1650.22 µg FAE g−1 DM in Ebners Rotkorn). Bound phenolic compounds represented 86.3% of the total ones. An extremely dry and warm ripening period had a negative impact on the synthesis of phenolic compounds. The highest concentration of total PAs was observed in spelt Ebners Rotkorn (681.75 µg g−1 DM) and the lowest in common wheat (396.05 µg g−1 DM). The total share of free and bound PAs was 5.7% and 74.8%, respectively. The extremely dry and very warm grain filling period had a more evident negative impact on the concentration of free PAs compared to bound forms. The dominant free PA was ferulic (70.48%), followed by syringic (9.30%), p-HBA (5.59%), sinapic acid (5.40%), salicylic (4.18%), p-coumaric acid (3.22%) and caffeic acid (1.93%). Spelt cultivar Ebners Rotkorn was distinguished by the highest concentration of free and bound forms of PAs.